Physical Activity of the Elderly in Light of the 2020 WHO Guidelines - Jakub P. Husejko; Maciej Strugała; Mateusz Modrzejewski; Mariusz Wąsicki; Kornelia Kędziora-Kornatowska; Marta Podhorecka (Rehabilitacja Medyczna, 2021)
Introduction: Demographic assessment in Poland allows to show progressive aging of society, which is further related to the growing number of people with cardiovascular diseases, cancer and disabilities of various origins. In November 2020, the World Health Organization (WHO) issued recommendations for physical activity which, for the first time, also apply to people suffering from chronic diseases and to those with disabilities. Compliance with the guidelines is part of prevention with regard to both chronic diseases and disabilities of various origins.